Preparação e caracterização de filmes finos de TiO2 dopados com nióbio pelo método sol-gel - Gustavo Henrique de Magalhães Gomes (2017)
Titanium dioxide (TiO2) is a multifunctional material widely studied, its properties can be modulated through the combination with other elements, allowing the development of materials with higher performance and increasing the technological application of material. In this context and the actual Brazilian scenario, where around 90% of the world niobium reserves are located in the country, it was made the insertion of niobium inside the structure of the titanium dioxide thin films, using a national and with low cost product. Several new formulations were developed, using titanium(IV) isopropoxide as titanium dioxide precursor and a niobium complexe (oxobisoxalatobisaquoniobate(V) hydrated) as source of the metal. Thin films were deposited in a glass substrate using the sol-gel process and dip-coating methodology. A systematic study was carried varying the calcination temperature between 200 and 500 °C, the number of layers (one to five), and the concentration of niobium of 0 to 5% in atomic ratio. The studied thin filmes were characterized by their optical, electronic, morphological and textural properties Optical and electronic properties were studied using ultraviolet-visible and ellipsometry spectroscopy, in order to determine the dielectric function, optical band-gap, thickness, roughness and transmittance of the thin films. The niobium doped thin films showed to be denser and more light absorbers. The X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM) and atomic force microscopy (AFM) were used in order to evaluate the modifications that the niobium insertion promote to the titanium dioxide matrix. An increase in the lattice parameters and the interplanar distance, shrinking of the particle and crystallite size, changes in the superficial morphology and roughness were observed for the doped thin films. The TiO2 and Nb:TiO2 thin films were tested by their hydrophilic, hydrophobic and photodegradation properties. In both tests, the doped thin film showed to be superior against the undoped thin film. Increasing the contact angle with water (superhydrophilic in the case of the thin film calcinated at 500 °C) and a first order rate constant almost two times bigger than the undoped thin film.